(untitled) (Journal of Engineering, 2011)
Thermal performance of closed wet cooling tower has been investigated experimentally and theoretically in this work. The theoretical model based on heat and mass transfer equations and heat and mass transfer balance equations which are established for steady state case. A new small indirect cooling tower was used for conducting experiments. The cooling capacity of cooling tower is 1 kW for an inlet water temperature of 38oC, a water mass velocity 2.3 kg/m2.s and an air wet bulb temperature of 26oC. This study investigates the relationship between saturation efficiency, cooling capacity and coefficient of performance of closed wet cooling tower versus different operating parameters such wet-bulb temperature, variable air-spray water flow ratio and cooling water inlet temperature. Results indicate that the capacity and saturation efficiency was found close to the related experimental results. Good agreement was obtained between the theoretical results and experimental measurements for the performance of small cooling tower.